Evaluation of Humoral Response of Emergency Unit Healthcare Workers after Third Dose of COVID-19 Vaccination - Irsan, Abror; Mardhia, Mardhia; Rialita, Ambar (Muhammadiyah Medical Journal, 2022)
Background:  Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), is an emerging disease that has become pandemic. Healthcare workers are vulnerable persons due to SARS-CoV-2 infection. Healthcare workers are a government priority in the COVID-19 vaccine program. Antibody titer evaluation to healthcare workers as the first liner is essential due to the risk of the job. Purposes: The study aims to assess IgG antibody humoral response in healthcare workers in the emergency unit of Anton Soedjarwo Hospital, Pontianak, before and after the third dose of the COVID-19 vaccine. Methods: This study was a descriptive study with a cohort method. Twenty-two healthcare workers in the Emergency Unit in Anton Soedjarwo Hospital, Pontianak, participated in the study. Three ml venous blood samples were collected from the participants in two periods to quantify IgG antibody titer. The first period was before the third dose of the COVID-19 vaccine, and the second period was one month after the third dose of the COVID-19 vaccine. Chemiluminescent Microparticle Immunoassay (CMIA) methods were used to quantification IgG antibodies against spike-receptor binding domain (S-RBD) protein of SARS-CoV-2 Results: One month before the third dose of the COVID-19 vaccine, the majority of IgG antibodies show seropositivity (90.91%), with most on range 50-10,000 AU/ml (54.55%). Two participants (9.09%) show IgG antibodies less than 50 AU/ml (seronegative). One month after the third vaccination dose, all participants (100%) elicit IgG antibodies. Based on the comparison of IgG antibody titer before and after the third dose of the vaccine, the majority (68.18%) showed increasing the IgG antibody titer after the third vaccine.  Conclusion: The third dose vaccine might effectively elevate immune response to SARS-CoV-2 infection.